Economy-Wide Implications of Direct and Indirect Policy Interventions in the Water Sector : Lessons from Recent Work and Future Research Needs - Dinar, Ariel (World Bank, Washington, DC, 2012)
Water is increasingly becoming a limiting factor for sustainable economic growth and development in many countries. Its allocation has significant impacts on overall economic efficiency, particularly with growing physical scarcity in certain regions. Greater water supply variability further increases vulnerability in affected regions. Water also has become a strategic resource involving conflicts among those who may be affected differently by various policies. This paper analyzes various policy interventions aimed at improving water allocation decisions, using a novel approach that incorporates macro and micro level considerations in a unified analytical framework. The framework facilitates assessment of various linkages among policies and their impacts within individual sectors and economy-wide. Drawing on country based studies in Morocco, South Africa, Turkey, and Mexico, the analysis reveals difficult tradeoffs among various policy objectives, including priorities placed on different sectors, regional advantages, and general economic efficiency gains versus broader social impacts. The comparison of policy impacts demonstrates the usefulness of the framework in information that policy makers can use to rank the policy interventions according to the emphasis placed on different policy objectives. The paper also compares approaches used in other studies that apply computable general equilibrium models in various contexts of water, environment and agriculture.